2016
DOI: 10.1371/journal.ppat.1005957
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and Mechanism for the MCR-1 Colistin Resistance

Abstract: Polymyxins are the last line of defense against lethal infections caused by multidrug resistant Gram-negative pathogens. Very recently, the use of polymyxins has been greatly challenged by the emergence of the plasmid-borne mobile colistin resistance gene (mcr-1). However, the mechanistic aspects of the MCR-1 colistin resistance are still poorly understood. Here we report the comparative genomics of two new mcr-1-harbouring plasmids isolated from the human gut microbiota, highlighting the diversity in plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
269
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 235 publications
(288 citation statements)
references
References 51 publications
11
269
0
8
Order By: Relevance
“…The pLS12 plasmid seems identical to the pE15004 plasmid isolated from a diarrhea inpatient's feces that we had analyzed earlier in 2016 ( Fig. 1B and 2B) (4,9). Sequence alignment suggested that the mcr-1-negative pSH146-32 plasmid might be an ancestor for the pLS12 and pmcr-1-IncX4 plasmids (Fig.…”
mentioning
confidence: 58%
“…The pLS12 plasmid seems identical to the pE15004 plasmid isolated from a diarrhea inpatient's feces that we had analyzed earlier in 2016 ( Fig. 1B and 2B) (4,9). Sequence alignment suggested that the mcr-1-negative pSH146-32 plasmid might be an ancestor for the pLS12 and pmcr-1-IncX4 plasmids (Fig.…”
mentioning
confidence: 58%
“…Unfortunately, it seems likely that the clinical use of carbapenems and colistin has been significantly challenged by the occurrence of mobilized colistin resistance determinant (MCR-1) in clinical carbapenem-resistant isolates producing New Delhi metallo- β -lactamase 1 (NDM-1) [6,7] or its variant NDM-5 [8,9]. In addition to the intrinsic determinants of colistin resistance (e.g., EptA [10,11] and ICR-Mo [12]), the transferable determinants (MCR-1 and MCR-2 [10,13,14]) consistently encode members of phosphoethanolamine (PEA)-lipid A transferases, which adopt a ‘ping-pong’ catalysis reaction in transferring of the PEA moiety to the 4ʹ-phosphate position of the lipopolysaccharide (LPS)-lipid A species anchored on bacterial surface [4,5]. …”
mentioning
confidence: 99%
“…The MCR-1 enzyme modifies the chemical structure of lipid A moiety on bacterial lipopolysaccharide by the addition of phosphoethanolamine, which in turn reduces the binding affinity to colistin (i.e., producing the colistin resistance) (1,18,19). To date, only one functional variant of MCR-1, MCR-1.2, has been reported (17).…”
mentioning
confidence: 99%